Retained State Shareholding in Chinese PLCs : Does Government Ownership Reduce Corporate Value? - Lihui Tian; Saul Estrin (Institute for the Study of Labor (IZA), 2005)
The role of government shareholding in corporate performance is central to an understanding of China?s newly privatized large firms. In this paper, we analyze shareholders as agents that can both harm and benefit companies. We examine the ownership structure of 826 listed corporations and find that government shareholding is surprisingly large. Its effect on corporate value is found to be negative, but non-monotonic. Up to a certain threshold, corporate value decreases as government shareholding stakes increase, but beyond this corporate value begins to increase. We interpret this in terms of ownership concentration and the advantages of government partiality.
Keywords: G32; G34; L33; G15; 330; government shareholding; corporate governance; China; Öffentliches Unternehmen; Privatisierung; Corporate Governance; Eigentümerstruktur; China